2020
DOI: 10.1021/acs.jafc.0c02717
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation Stimulation Ability and Osteogenic Activity of Low Molecular Weight Peptides Derived from Bovine Gelatin Hydrolysates

Abstract: It has been recognized that collagen peptides of MW 878 Da (CP1) promote osteoblast proliferation and mineralization. The objective of this study is to identify the peptides responsible for proliferation of osteoblast growth, enhancement of ALP (alkaline phosphatase) activity in osteoblasts and promotion of osteoblast mineralization. To this end, the CP1 were fractioned by a series of chromatography procedures, and 51 peptides from the fraction possessing the most powerful cell proliferation ability were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…In agreement with these results, Wang and co-workers also observed a higher cell growth rate after 24 h compared to 48 and 72 h by studying the proliferation effects of peptides from bovine gelatin hydrolysate on MC3T3-E1 cell line, indicating that peptides can stimulate cell growth in a short time [22]. None of the peptides examined showed significant cytotoxicity throughout the study, and the peptides VL-9, VY-9, VW-9, VF-9, VCK-9, VHK-9, VYK-9, SK-7, and YR-10 significantly increased cell growth.…”
Section: Macrophage Viabilitysupporting
confidence: 71%
“…In agreement with these results, Wang and co-workers also observed a higher cell growth rate after 24 h compared to 48 and 72 h by studying the proliferation effects of peptides from bovine gelatin hydrolysate on MC3T3-E1 cell line, indicating that peptides can stimulate cell growth in a short time [22]. None of the peptides examined showed significant cytotoxicity throughout the study, and the peptides VL-9, VY-9, VW-9, VF-9, VCK-9, VHK-9, VYK-9, SK-7, and YR-10 significantly increased cell growth.…”
Section: Macrophage Viabilitysupporting
confidence: 71%
“…In general, the size of peptides is a vital factor affecting bioactivity of HC [ 8 ]. Peptides of smaller sizes mostly exhibited higher bioactivities, especially osteoblast proliferation activity [ 9 , 10 ]. In addition, short chain peptides could be rapidly digested and absorbed in the human body [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased proliferation of cells indicated that HC could induce the proliferation of osteoblast cells. Peptides rich in hydrophobic AAs and imino acids might play a vital role in proliferation [ 9 , 12 ]. Moreover, HC rich in Pro-Hyp and Pro-Hyp-Gly have been shown to induce the growth of osteoblast cells [ 12 , 13 ], and a previous work has demonstrated the presence of these peptides in HC from sea bass skin [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations